Dispersion-enhancing surface treatment of AuNPs for a reduced probe loading and detection limit using t-SPR detection. Issue 18 (9th August 2021) - Yeung, Wing Kiu; Lo, Shu-Cheng; Wang, Sheng-Hann; Wei, Pei-Kuen; Cheng, Ji-Yen
Abstract : A nanoplasmonic platform for oligonucleotide detection is developed. Functionalized unmodified PEG-Au was used as an SPR signal amplifier. The SPR sensor exhibited high sensitivity with a detection limit of 100 aM. The platform was able to detect a single mismatch sequence. Abstract : COVID-19 has shown that a highly specific and rapid diagnostic system is a necessity. A spectral imaging-based surface plasmon resonance (SPRi) platform with an integrated microfluidic biosensor to detect oligonucleotide sequences has been proposed to be a promising alternative for infectious diseases due to its safe and straightforward use. Approaches to reduce the DNA probe loading onto gold nanoparticles with various types of polyethylene glycol (PEG) were explored. Here, we demonstrated the stability of functionalised gold nanoparticles with unmodified PEG whilst lowering the probe loading density. The system was evaluated by performing the detection of a mimicking COVID-19 target sequence, single point-mutation sequence and fully mismatch sequence. Highly specific binding of the mimicking COVID-19 target sequence was observed and analysed by the spectral imaging SPR approach. Our work has demonstrated the potential of a controlled probe density using unmodified PEG as an especially promising functionalisation strategy in SPR spectral imaging assays.